Plant Protection Practises and Their Impact on Environment - Yildirim, Ismet (Journal of Central European Green Innovation, 2023)
The world population is increasing by 81 million every year and people need more agricultural production to avoid hunger. Despite modern farming methods, where advanced technologies and new production systems such as soilless agriculture are applied, production seems far from meeting the nutritional needs of people today or in the future. Although phytopathogens, insects and weeds, which cause significant yield and quality losses in agricultural products, are struggled today, it is estimated that the total loss of crops is 36.5% in the world every year due to these pests. Plant protection practices (cultural measures, physical control, legal measures, biological control, chemical control, alternative control) are carried out against pests in order to prevent product yield and quality losses in agriculture. Among these applications, chemical control is the most effective control method against pests, the results of which can be seen in a short time. However, especially in conventional agriculture, irregular and intensive pesticide applications made to protect yield and quality with economic concerns cause environmental pollution and deterioration in soil, water resources and troposphere ecosystems. In this review, the effects of plant protection practices on non-target organisms in different ecosystems are presented.
Keywords: plant protection; pesticides; environmental pollution; non-target organism; crop production